1999
DOI: 10.1021/jo981826a
|View full text |Cite
|
Sign up to set email alerts
|

Organic Synthesis in Water/Carbon Dioxide Emulsions

Abstract: The synthetic reaction between a hydrophobe, benzyl chloride, and a hydrophilic nucleophile, KBr, is reported in water-in-carbon dioxide (w/c) and carbon dioxide-in-water (c/w) emulsions. Emulsions containing equal amounts of water and CO2 were formed with both anionic perfluoropolyether ammonium carboxylate (PFPE COO-NH4 +) and nonionic poly(dimethylsiloxane)-g-poly(ethylene oxide) and poly(butylene oxide)-b-poly(ethylene oxide) surfactants, without the need for any added cosolvent. Higher yields of benzyl br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 21 publications
1
46
0
Order By: Relevance
“…The emulsion catalysis functions as highly dispersed nanoreactors and behaves like homogeneous catalysis. The biphasic catalytic systems are different from those reported by other groups [14][15][16], the amphiphilic catalyst can be assembled in the interface of emulsion, droplets in the reaction system, not in the continuous phase or inside the emulsion droplet. In addition, the emulsion droplets can be demulsified by centrifugation and easily separated and recycled.…”
Section: Selective Oxidation Of Real Diesel In W/o Emulsionmentioning
confidence: 67%
See 3 more Smart Citations
“…The emulsion catalysis functions as highly dispersed nanoreactors and behaves like homogeneous catalysis. The biphasic catalytic systems are different from those reported by other groups [14][15][16], the amphiphilic catalyst can be assembled in the interface of emulsion, droplets in the reaction system, not in the continuous phase or inside the emulsion droplet. In addition, the emulsion droplets can be demulsified by centrifugation and easily separated and recycled.…”
Section: Selective Oxidation Of Real Diesel In W/o Emulsionmentioning
confidence: 67%
“…One of the most general and efficient methods that can overcome this disadvantage is to use surfactants, which solubilize the reactants or form colloidal dispersion in reaction systems. The biphase systems thus obtained include phase-transfer catalysis [4][5][6][7][8], micellar catalysis [9][10], and microemulsion [11][12][13] or emulsion [14][15][16][17][18] according to the different reaction circumstances.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the past few years several key aspects of the PFPE/scC0 2/H 2 0 system have been investigated, including their phase equilibria, water pool and micelle shape, and internal dynamics [38], the pH within an unbuffered PFPE water pool [39] and a means to control the water pool pH within PFPE micelles [40]. Several researchers have also shown that one can use the PFPE/C0 2 /H 2 0 system to perform inorganic [41] and organic [42,43] reactions directly within the micelle water pool. Researchers have also used these micelles to prepare tailored, uniform CdS nanoparticles [44].…”
Section: The Futurementioning
confidence: 99%